2014
DOI: 10.1590/1982-0216201412812
|View full text |Cite
|
Sign up to set email alerts
|

Alterações no controle motor mandibular e cervical de crianças com paralisia cerebral

Abstract: Objetivo: analisar a atividade elétrica dos músculos Temporal e Masseter e o padrão de postura e movimento de cabeça e mandíbula de crianças com Paralisia Cerebral (PC).Métodos: a amostra deste estudo compreendeu 32 voluntários com PC espástica e com Desenvolvimento Típico, com a faixa etária de 7 a 13 anos de idade, caracterizados com base na Classificação de Angle e Critério de Diagnóstico para Pesquisa das Disfunções Temporomandibulares (RDC/TMD). De forma simultânea, foram avaliadas a postura e movimentaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…However, these analyses are based on evidence and assessments of healthy individuals (KIRVESKARI, ALANEN, KARSKELA et al, 1988;MARIA, 2002;ROBINSON, 1966). Schmidt, Briesemeister and Ries (2014), in a study conducted on 16 children with CP, observed that during chewing cycle maintenance, there is greater asymmetry present in the pterygoid muscles' electric activity in relation to masseter muscles, associated with further extension and forwarding of the head. However, patients have showed few signs of TMD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these analyses are based on evidence and assessments of healthy individuals (KIRVESKARI, ALANEN, KARSKELA et al, 1988;MARIA, 2002;ROBINSON, 1966). Schmidt, Briesemeister and Ries (2014), in a study conducted on 16 children with CP, observed that during chewing cycle maintenance, there is greater asymmetry present in the pterygoid muscles' electric activity in relation to masseter muscles, associated with further extension and forwarding of the head. However, patients have showed few signs of TMD.…”
Section: Resultsmentioning
confidence: 99%
“…However, patients have showed few signs of TMD. According to the author, stimulating masticatory muscles decreases the likelihood of craniofacial disorders found in patients with CP (SCHMIDT, BRIESEMEISTER and RIES, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control and mobility of the oral structures for feeding and swallowing, are linked to head -trunk control and stability. Low postural tone and poor proximal neck and trunk stability cause slower and longer eating, resulting in lower food intake (47). Gisel et al results had proved interaction between oral structures and postural control of the "whole body."…”
Section: Effect Of Neck and Trunk Stabilization On Feeding Function I...mentioning
confidence: 98%
“…Em pacientes distróficos é possível notar o aumento da concentração de cálcio no interior da célula, desencadeando uma contração máxima do músculo, provocando um déficit metabólico local, este metaboliza gás carbônico no lugar de oxigênio, ou seja, ocorre uma anaerobiose, com produção mínima de energia, 2 ATP e ácido láctico, essa falta de fonte de energia acomete os sarcômeros que não possuem ATP suficiente para ativar a bomba de Cálcio, impedindo seu retorno para o retículo sarcoplasmático e procedendo uma contração muscular máxima 3 Levando ao estimulo do sistema nervoso central por meio de fibras aferentes moduladas no complexo de interneurônios. Logo, ativando outras áreas neuronais, promovendo então uma dor referida, concorrendo para alterações miofasciais que levam a alterações a distância 4 .…”
Section: Introductionunclassified